Effectiveness of daily subjective wellness measurements via mobile applications in predicting perceived exertion and training load - Bertschy, M. J. W. (University of Texas, 2020)
This study aimed to examine the effectiveness of pre-training subjective wellness, measured by a mobile application, in predicting perceived exertion (RPE) and training load for collegiate female soccer players in all types of training sessions throughout a soccer season. Fifty training sessions over 10 weeks period involving 27 subjects were analyzed. Before each training session, players would self-report wellness measurements (sleep quality, stress, mood, soreness, fatigue, sleep duration) through a questionnaire on a mobile application. External training load was measured by GPS technology (active time, distance, run distance, accelerations, decelerations). RPE was self-reported immediately after training sessions by mobile application. Generalized linear models found that wellness scores had a significant effect on RPE, but no effect on training load. A wellness score increase of 1 point corresponded with a (95%CI=0.11 - 0.82, p=.010) increase in RPE. Wellness components stress and mood had a significant effect on RPE, a 1 point increase in each corresponded to a (95% CI=0.17 - 0.668, p=.001 and 95% CI=0.03 - 0.74, p=.035) increase in RPE, respectively. It was shown that perceived wellness had a significant effect on predicting RPE while accounting for training load, and psychosocial components (stress and mood) of wellness played the most influential role. The results suggest that monitoring collegiate student-athlete wellness may be more helpful in regulating player internal load than monitoring external load alone, and that lowering player stress and increasing happiness may also lower internal load.